A Comprehensive Epidemiological Research for Clinical Vibrio parahaemolyticus in Shanghai - Li, Huan; Tang, Rong; Lou, Yang; Cui, Zelin; Chen, Wenjing; Hong, Qing; Zhang, Zhaohuan; Malakar, Pradeep K.; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2017)
Vibrio parahaemolyticus is one of the most important pathogen for seafood-borne gastroenteritis in Shanghai and the rest of the world. A total of 42 V. parahaemolyticus strains were isolated from 1900 fecal specimens collected from patients in Shanghai hospital presenting from January 2014 to December 2015. All isolates were evaluated for potential virulence factors [tdh, trh, and type three secretion system (T3SS) genes], typed using multilocus sequence typing (MLST) and screened for antimicrobial resistance phenotype and genotype. And for the first time, the relationship between virulence, genetic diversity and antimicrobial resistance of these isolates were identified. The results showed that 37 isolates carried the tdh gene (88.1%) and only seven isolates were positive for the trh gene. The T3SS1 and T3SS2 genes were detected in all strains and only trh-positive isolates are also containing the T3SS2β genes. MLST analysis of the 42 Shanghai isolates identified 20 sequence types (STs) with 16 novel STs and that these clinical V. parahaemolyticus strains showed high degrees of genetic diversity. All isolates expressed high levels of resistance against Ampicillin (100.0%), Streptomycin (100.0%), Cephazolin (92.9%), Kanamycin (92.8%) and Amikacin (90.5%), and eight out of 38 resistance genes (SHV, tet(B), strA, qnrA, gryA, qnrB, sulI, sulII) were detected in at least two isolates. This study confirms that antimicrobial resistance of clinical V. parahaemolyticus isolates is greater than those of environmental isolates. Furthermore, no clear correlation between antimicrobial resistance and virulence or genetic diversity was found in this study. These results add to epidemiological data of clinical V. parahaemolyticus isolates in Shanghai and highlight the need for additional mechanistic studies, especially antimicrobial resistance, to reduce the burden of disease caused by this pathogen in China.